Soil inhabiting nematodes of the genera Trischistoma, Tripylina and Tripyla from México and the USA with descriptions of new species (Journal of Nematode Morphology and Systematics, 2012)
Five species of the family Tripylidae were collected; two from the Biosphere Reserve at San Fernando, LosTuxtlas, Veracruz, Mexico: Trischistoma veracruzense sp. n., and Tripyla tropica sp. n.; two from soil in the Napa Valley, California, USA: Tripyla alaecaudata sp. n., and Tripyla napaensis sp. n., and one from the University of California, Davis, Student Farm: Tripylina arenicola. In all cases the habitats are moist soils from either natural seepage (Napa), irrigation (Davis) or rainfall (Mexico). Trischistoma veracruzense sp. n. is characterised by females that are slightly longer than males, average 1.2 vs 1.0 mm, the absence of cervical setae, the long, wide post-uterine sac, abundant males without pre-cloacal papillae and producing oval sperm cells. In Tripylina arenicola the subventral teeth are posterior to the dorsal tooth and there is a small ventromedian cervical seta close to the anterior end. This population differs from type material in having a pre-anal ventral papilla. Tripyla tropica sp. n. is characterised by a stomatal chamber, a posteriorly-hooked dorsal tooth with subventral teeth posterior to it, a large cardia, the absence of sclerotised structures in the vulva and the heavily muscular vagina. The male lacks ventromedian papillae, has curved spicules and a straight gubernaculum. Tripyla alaecaudata sp. n. is distinguishable from all other species of the genus by the lateral alae in the juvenile, female and male tails, and a pair of papillae in the tail region. Tripyla napaensis is characterised by tiny subventral denticles anterior to the wedge-shaped dorsal tooth, vulva with slightly protruding lips, spermatheca oval with oval-shaped sperm cells, male with 14 ventral papillae, and tail in both sexes tapering in anterior region and becoming narrowly cylindrical in posterior third, ending in a long spinneret. Keys to species of Trischistoma and Tripyla are provided. Representatives of the new Tripyla and Trischistoma species are each distinct in pairwise comparisons of small subunit (SSU) ribosomal DNA sequences, supporting their morphologically-based differential diagnosis. Phylogenetic analyses of the sequences place the new Tripyla and Trischistoma species within clades representing greater species diversity of their respective genera. The molecular data support taxonomic reorganization of Tripylidae into at least two clades, one including Tripylina, Trischistoma and Trefusia and another including Tripyla, Tripylella, Paratripyla and Tobrilus.